Historical Development of Skiing: Case Study in Durmitor Area - Rajko Milašinović; Duško Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
The objective of this study is the history of skiing, while the main goal will be the historical development of skiing in the mountain Durmitor area in Montenegro. The study consists two goals. The first goal is the emergence of the first ski in the Montenegro and benefits that are brought. The second and the main goal is the occurrence and development of skiing and ski sports in the territory of mountain Durmitor. During the making of this study, the authors used descriptive method with consulting of competent literature. The previous authors' experience in this field was also so useful. Moreover, the author used the analytic method and parallel method that is the most productive if you make some inferences about some appearance. The main outcome of this study was showing of historical progress of ski sports in the territory of mountain Durmitor from early beginnings to the modern Olympic skiing. Skis and ski sport were early appeared in the region of Mount Durmitor. The mountain and the region around it, are very rich with slopes with Olympic diameter, with plenty of snowfall and long winters. However, lack of financial investment, channeling money to other centers, led to the fact that the skiing in this area is at a low level.